Clinician's manual on axial spondyloarthritis - Sieper, Joachim (Springer Healthcare Ltd., 2014)
A thorough guide for readers to quickly gain an update on standard diagnosis and treatment methods for axial spondyloarthritis. Approximately 80 illustrations and images are used throughout the text to exemplify the disease and diagnostic and treatment algorithms. Easily accessible text and tables review the current treatment recommendations and emerging treatment options based on recent clinical trials.